In Pulmonary Arterial Hypertension, Reduced BMPR2 Promotes Endothelial-to-Mesenchymal Transition via HMGA1 and Its Target Slug. Issue 18 (3rd May 2016) - Hopper, Rachel K.; Moonen, Jan-Renier A.J.; Diebold, Isabel; Cao, Aiqin; Rhodes, Christopher J.; Tojais, Nancy F.; Hennigs, Jan K.; Gu, Mingxia; Wang, Lingli; Rabinovitch, Marlene
Abstract : Background—: We previously reported high-throughput RNA sequencing analyses that identified heightened expression of the chromatin architectural factor High Mobility Group AT-hook 1 (HMGA1) in pulmonary arterial endothelial cells (PAECs) from patients who had idiopathic pulmonary arterial hypertension (PAH) in comparison with controls. Because HMGA1 promotes epithelial-to-mesenchymal transition in cancer, we hypothesized that increased HMGA1 could induce transition of PAECs to a smooth muscle (SM)–like mesenchymal phenotype (endothelial-to-mesenchymal transition), explaining both dysregulation of PAEC function and possible cellular contribution to the occlusive remodeling that characterizes advanced idiopathic PAH. Methods and Results—: We documented increased HMGA1 in PAECs cultured from idiopathic PAH versus donor control lungs. Confocal microscopy of lung explants localized the increase in HMGA1 consistently to pulmonary arterial endothelium, and identified many cells double-positive for HMGA1 and SM22α in occlusive and plexogenic lesions. Because decreased expression and function of bone morphogenetic protein receptor 2 (BMPR2) is observed in PAH, we reduced BMPR2 by small interfering RNA in control PAECs and documented an increase in HMGA1 protein. Consistent with transition of PAECs by HMGA1, we detected reduced platelet endothelial cell adhesion molecule 1 (CD31) and increased endothelial-to-mesenchymal transition markers, αSM actin, SM22α, calponin, phospho-vimentin, and Slug. The transition was associated with spindle SM-like morphology, and the increase in αSM actin was largely reversed by joint knockdown of BMPR2 and HMGA1 or Slug. Pulmonary endothelial cells from mice with endothelial cell–specific loss of Bmpr2 showed similar gene and protein changes. Conclusions—: Increased HMGA1 in PAECs resulting from dysfunctional BMPR2 signaling can transition endothelium to SM-like cells associated with PAH. Abstract : Supplemental Digital Content is available in the text.